Die Uniekheid van ’n Reformatoriese Lewensvisie (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2008)
This article is focussed on the contents of a Christian worldview. The motivation for this investigation is the problem that Christians today have very little impact outside the small circle of private life, family and church. The reason for their irrelevance in the public sphere is not a lack of Christian worldviews, but the impotence of most Christian worldviews which are dualistic in nature. What is needed is a comprehensive and integral Christian worldview, firmly rooted in the message of the Bible. Can a reformational worldview qualify for this position? The essay therefore investigates the unique characteristics of a Christian-reformational worldview. The conclusion is that such a worldview can be a genuine worldtransformative worldview. It not only informs our minds, fires our imagination and moves our hearts, but can also shape our culture.